ABUNDANCE AND DIVERSITY OF PHYTOPLANKTON IN THE WATERS OF TELUK LECAH VILLAGE, RUPAT, BENGKALIS - Anwar, Sagita; Mulyadi, Aras; Eff, Irwan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
The aim of carrying out the research is to determine the abundance and diversity of phytoplankton. The method used in this research is a survey method, namely data collection, documentation, and direct observation in the field. Samples were analyzed at the Marine Biology Laboratory of Riau University. The results of the research show that there are six types of phytoplankton found in the waters of Teluk Lecah Village, Rupat District, Bengkalis Regency, namely Synedra sp, Dactylococcopsis sp, Nitzschia sp, Tribonema sp, Cylindrotheca sp, and Rhizosolenia sp. The first highest phytoplankton abundance was at station II, with an abundance of 0.1660, followed by the second highest phytoplankton abundance at station I, namely the residential area, with an abundance of 0.1494 Ind/L, while the lowest phytoplankton abundance was at station III, namely at the harbor with an abundance of 0. ,0996 Ind/L. The species diversity index at stations I and III, H' > 3, means the level of species diversity is high and the water conditions are not polluted. At station II, 1 ≤ H' ≤ 3 means the level of species diversity is moderate, and the water conditions are lightly polluted. It can be concluded that the H' value still meets the criteria. The species diversity index at all stations, E > 0.5, means that the uniformity of organisms is in balance, and there is no competition for certain places or food. It can be concluded that the E value also meets the criteria. Species dominance index at all stations, D < 0.5 means no dominant species exists